Fostering College Readiness: An Ethnography of a Latina/o Afterschool Program. Issue 7 (September 2019) - Tichavakunda, Antar A.
There are two, related types of college readiness: (a) cognitive—students' test scores and grades and (b) noncognitive—students' academic mind-sets, behaviors, and motivation. This study uses an ethnographic approach to examine how an afterschool program for Latina/o high school youth fosters noncognitive factors of college readiness. Based on over 80 hr of participant observation and 31 semistructured interviews, this work demonstrates how an afterschool program acts as a supplement to students' noncognitive factors of college readiness. The findings also suggest that afterschool programs for high school youth can act as hubs of behavioral nudges toward noncognitive college readiness and access.